Structural basis of TFIIH activation for nucleotide excision repair - Goran Kokic (Nature Portfolio, 2019)
The NER machinery contains the multisubunit transcription factor IIH (TFIIH) that opens the DNA repair bubble, scans for the lesion, and coordinates excision of the damaged site. Here the authors resolve the cryo-electron microscopy structure of the human core TFIIH-XPA-DNA complex and provide insights into its activation.